2017
DOI: 10.3748/wjg.v23.i25.4491
|View full text |Cite
|
Sign up to set email alerts
|

Eubiotic properties of rifaximin: Disruption of the traditional concepts in gut microbiota modulation

Abstract: Antibiotics are usually prescribed to cure infections but they also have significant modulatory effects on the gut microbiota. Several alterations of the intestinal bacterial community have been reported during antibiotic treatment, including the reduction of beneficial bacteria as well as of microbial alpha-diversity. Although after the discontinuation of antibiotic therapies it has been observed a trend towards the restoration of the original condition, the new steady state is different from the previous one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
96
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 94 publications
1
96
0
15
Order By: Relevance
“…In rats on rifaximin, the transient reductions in stool coliform counts recover after rifaximin interruption, while rifaximin appears to produce durable reductions in duodenal bacteria [21][22][23][24]. Further studies in animal models, culture studies and metagenomic analyses have demonstrated an increase in Bifidobacterium, Faecalibacterium prausnitzii and Lactobacillus abundance after rifaximin treatment, also with no significant changes in the overall gut microbiota composition [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In rats on rifaximin, the transient reductions in stool coliform counts recover after rifaximin interruption, while rifaximin appears to produce durable reductions in duodenal bacteria [21][22][23][24]. Further studies in animal models, culture studies and metagenomic analyses have demonstrated an increase in Bifidobacterium, Faecalibacterium prausnitzii and Lactobacillus abundance after rifaximin treatment, also with no significant changes in the overall gut microbiota composition [21].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies in animal models, culture studies and metagenomic analyses have demonstrated an increase in Bifidobacterium, Faecalibacterium prausnitzii and Lactobacillus abundance after rifaximin treatment, also with no significant changes in the overall gut microbiota composition [21]. In patients with other gastrointestinal diseases (e.g., diverticular disease, irritable bowel syndrome), the body of knowledge on the mode of action of rifaximin is larger.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both bacterial culture and 16S sequencing data showed Bifidobacterium as highly prevalent in all models, with rifaximin exposure causing a decline in models A and C, and an increase in model B. Susceptibility of Bifidobacterium populations to each rifaximin formulation could explain these differences, as Bifidobacterium genus has been shown to be highly resistant to rifaximin, with MICs increasing up to 25 mg l -1 during antibiotic exposure [35, 36]. As observed in patient studies, [13, 15, 35] our culture and sequencing data showed recovery of the microbial populations affected by rifaximin instillation, although differences in the relative abundance of some bacterial groups were observed.…”
Section: Discussionmentioning
confidence: 92%